Impact of Productivity and Quality of Welds Produced by the Submerged Arc Welding Process are Affected by Type of Filler Wire, Wire Size, and Welding Current - Upendra Kumar; Lokesh Singh (International Journal of Scientific Research in Mechanical and Materials Engineering, 2024)
Submerged Arc Welding (SAW) process gives more benefits over conventional arc welding processes (viz. better quality, productivity, coverage of different materials/shapes/sizes). SAW is used to deposit more than 10% of the weld metal all over the world. But the need and the pressure to find more effective welding techniques, to enhance the overall productivity, to make high-quality defect-free welds and to improve the welding cost economy is increasing every day. In this work, three sizes (2.4, 3.2, 4.0 mm diameter) of both solid wire and MCTW were tested by Bead on Plate welding technique over its full usable current range and productivity and quality parameters at various current levels were investigated, to find the most optimum wire form/size/current combination that gives high productivity as well as high quality and 3.2mm diameter metal cored tubular wire welded at 650A current is the result. This combination has been verified on a 25 mm thick Butt Joint Approval Test procedure using traditional single wire DCEP SAW system as well as on a 25 mm thick. Solid and Metal Cored Tubular, sizes: 2.4, 3.2, 4.0 mm with its fullest welding current range that gives acceptable weld beads which can be used for single or multi-pass/layer welding applications involved in groove or fillet or any combinations of weld joints. Using this research study findings, SAW can be now employed on welding applications which demands high quality as well as productivity, within the parameters/wire/flux evaluated.